THE EFFECT OF FORAGE MIXTURE AND GIBBERLIC ACID ON GREEN FORAGE YIELD AND GROWTH CHARACTERS OF BARLEY AND BERSEEM CLOVER - Almubarak , Nadir F.; Yousif, Adnan Y. (Diyala Agricultural Sciences Journal, 2011)
The experiment was carried out at the experimental farm of college of Agriculture – University of Diyala during the winter season of 2009 – 2010. to study the effect of forage mixture which represent the first factor with different ratios of seeding rate – barley Hordeum vulgare L var.Ibba99 which belong to Poaceae family and berseem(Egyptian clover )Trifolium alexendrinum L var.miskawi from Fabaceae family. The mixture ratios was : 1- 75% barley + 75% berseem clover (first mixture) 2- 50% barley + 100% berseem clover (second mixture ) The second factor was Gibberellic acid with 0.01cncentration, , and without GA3.The planting date was 15/10/2009 .The data reported for the flowing traits,Green forage yield kg/ha – Maximum height of barley plants/ cm – Maximum height of berseem plants/cm – Number of barley tillers /m2 – number of berseem stems/m2. The data were analyzed statistically with SPSS system.LSD were calculated to first. The result show that the difference in the ratio of each crops barley and berseem clover in the mixture was with clear effect in the growth characteristics ,whereas growth regulator gave increase in average of high plant and decrease of tillers to each crop in the mixture , while the speed of green fodder growth increased witch conducted to effect the forage yield positively , the use of second mixture gave heights increase in average of green forage yield to all cutting which reached to44.4% , 42.4% , 33.3% , 27,5% respectively , while the second mixture with growth regulator gave high increase in average of green forage yield which reached to 71% , 66.8% , 51.3% to the first three cutting respectively.